ERISAN TARANGKAMBREI: INTERPRETATION OF THE YAPEN ISLANDS, PAPUA TRADITION THROUGH CONTEMPORARY DANCE CREATION - Welly Kadiwaru; Peradantha Ida Bagus Gede Surya; Winerungan Febiola Karolina (Institut Seni Indonesia Bali, 2026)
The Erisan Tarangkambrei tradition in Papuma Village, Yapen Islands, Papua, is a cultural ritual marking a girl’s first ear piercing as a symbol of maternal kinship. However, under the pressure of globalization, its cultural values risk decline. This study aims to interpret the symbolic and philosophical values of Erisan Tarangkambrei into the medium of contemporary dance as an effort to preserve local culture. Using a qualitative autoethnographic approach, this research applies artistic exploration, choreography development, and critical reflection to translate the ritual into contemporary dance form. Data were collected through the creator’s reflective notes and audiovisual observation, analyzed through cultural interpretation and literature synthesis. The study identifies five choreographic sections that reflect the ritual sequence, namely (1) Spiritual and Mental Preparation, (2) Transition and Tension, (3) The Piercing Moment, (4) Togetherness, and (5) Reflection. These sections form a solo dance that employs a contemporary approach while maintaining the traditional symbolism of the ritual. This research demonstrates that cultural rituals can be revitalized through artistic transformation, enriching Indonesia’s contemporary dance repertoire and serving as an educational model for cultural preservation through creative expression.